Peningkatan Komunikasi Matematis dan Kemandirian Belajar Siswa melalui Pendekatan Problem Posing berbantuan Mind Map - Purwanti Purwanti; Anizar Ahmad (Universitas Syiah Kuala, 2016)
The purpose of this study to determine the increase of mathematical communication skills and independent learning that students acquire learning using learning approach problem posing aided mind map. This study used an experimental method with quantitative approach to research design pretest-posttest control group design. The study population was all students of class VII Islamic Solidarity School Jantho Aceh Besar. Sampel consists of two classes, namely the experimental class and control class taken with random sampling technique. To determine the increase in communication and independent learning ability of students between the group problem posing approach aided by a group mind map problem posing without a mind map used the t-test at the 0.05 significance level. The results showed that the increase in mathematical communication skills and independent learning that students acquire learning by problem posing approach aided mind map better than students who received no mind problem posing approach. Problem posing approach aided the mind map in learning can improve communication skills and independence of student learning mathematical form rather than the problem posing without a mind map. Aided learning approach problem posing a mind map can be used as an alternative learning that can improve mathematical communication skills and student learning independence.